The Influence of Web-Based Spiritual Problem Solving on the Prevention of Suicidal Risk among University Students - Siti Khadijah; Ah Yusuf; Hanik Endang Nihayati; Esti Yunitasari (Jurnal Ners, 2021)
Introduction: Suicide is a health phenomenon that is currently increasing, especially in young adults aged 15-29 years. The spiritual aspect in the form of belief in God is one way to prevent suicide. This study was conducted to determine the effect of web-based spiritual problem solving on the prevention of suicide risk in college students.Methods: The research design used a pre-experimental one-group pre-post-test. The sample was 59 respondents using the purposive sampling technique. The independent variable was web-based spiritual problem solving, and the dependent variable was suicide risk prevention. The intervention was delivered via the web using PowerPoint media, inspirational videos, and counseling for approximately one month with four sessions. Data were collected using a questionnaire and analyzed using the Wilcoxon sign rank test.Results: Web-Based Spiritual Problem Solving significantly decreases suicide risk with a p-value of 0.000 (p <0.05).Conclusion: Web-Based Spiritual Problem Solving has been shown to be effective in reducing students’ suicide risk. This web intervention can be used for 24 hours and specifically for counseling and two-way communication on the web; privacy is maintained because of a hidden identity, which is seen in code when interacting with counselors so as to minimize stigma